1998
DOI: 10.1021/bi971558v
|View full text |Cite
|
Sign up to set email alerts
|

Depth Profiles of Pulmonary Surfactant Protein B in Phosphatidylcholine Bilayers, Studied by Fluorescence and Electron Spin Resonance Spectroscopy

Abstract: Pulmonary surfactant-associated protein B (SP-B) has been isolated from porcine lungs and reconstituted in bilayers of dipalmitoylphosphatidylcholine (DPPC) or egg yolk phosphatidylcholine (PC) to characterize the extent of insertion of the protein into phospholipid bilayers. The parameters for the interaction of SP-B with DPPC or PC using different reconstitution protocols have been estimated from the changes induced in the fluorescence emission spectrum of the single protein tryptophan. All the different rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 44 publications
2
60
0
Order By: Relevance
“…SP-B, on the other hand, is less hydrophobic than SP-C and does not form transmembrane structures as SP-C does. It has been estimated that in the membrane and film of natural PS, SP-B likely interacts with the phospholipid molecules through the main axis of its amphipathic helical segments orientated in parallel to the plane of the lipid bilayers; 37 however, SP-C, being an even more hydrophobic protein, most likely assumes a transmembrane orientation. Our MD simulations suggest that each of these proteins in the PS corona may assume a molecular orientation similar to that in the PS membranes.…”
Section: Resultsmentioning
confidence: 99%
“…SP-B, on the other hand, is less hydrophobic than SP-C and does not form transmembrane structures as SP-C does. It has been estimated that in the membrane and film of natural PS, SP-B likely interacts with the phospholipid molecules through the main axis of its amphipathic helical segments orientated in parallel to the plane of the lipid bilayers; 37 however, SP-C, being an even more hydrophobic protein, most likely assumes a transmembrane orientation. Our MD simulations suggest that each of these proteins in the PS corona may assume a molecular orientation similar to that in the PS membranes.…”
Section: Resultsmentioning
confidence: 99%
“…However, a molecular structure of SP-B, the only member of the saposin family that is permanently associated with membranes, is still not available despite the fact that some molecular modelling efforts have been reported [69,70]. Numerous studies have approached the analysis of structural determinants in SP-B by means of indirect techniques such as circular dichroism [71,72] [73], fluorescence [74] or infrared spectroscopies [75,76], or electron spin resonance (ESR) [77]. The protein structure is dominated by a 40-50% "-helix, predicted to be in the form of amphipathic helical segments with well-defined polar and non-polar faces.…”
Section: Structure-function Relationships Of Sp-bmentioning
confidence: 99%
“…Although previous studies have shown that solvent-spread SP-C/phospholipid monolayers are similar to monolayers adsorbed from bilayers (Nag et al 1996), this has not been demonstrated for SP-B-containing systems. In determining potential equivalence for SP-B-containing ®lms formed by spreading versus adsorption, one must consider that the nature of the interaction of SP-B with phospholipid bilayers and its consequent surface activity is dependent on the method used to reconstitute lipid-protein samples (Cruz et al , 1998.…”
Section: Introductionmentioning
confidence: 99%